Advanced heart failure therapies in patients with stable HIV infection. Issue 4 (12th February 2020) - Brozzi, Nicolas A.; Simkins, Jacques; Cifuentes, Renzo O.; Ghodsizad, Ali; Thakkar Rivera, Nina; Loebe, Matthias
Abstract: Background: Human immunodeficiency virus (HIV) infection affects nearly 38 million people worldwide. Patients living with HIV (PLHIV) on modern highly active antiretroviral therapy face significant morbidity and mortality related to the progression of chronic diseases, which lead to an increase in the burden of end‐stage organ disease and organ failure. PLHIV present a two fold increased risk of heart failure as compared with the general population, with a prevalence of clinical heart failure of 6.5 %. Orthotopic heart transplantation (OHT) is rarely performed in HIV‐positive patients despite the fact that HIV‐associated cardiomyopathy is a major long‐term complication of HIV infection. Material and Methods: We present a case of PLHIV presenting with decompensated heart failure, requiring initial therapy with left ventricular assist device, followed by heart transplantation, accompanied by an update on current concepts, and experience in the field. Discussion and Conclusion: HIV‐associated cardiomyopathy is a major long‐term complication of HIV infection. LVAD support or OHT should also be encouraged among HIV‐positive patients as current data indicates that AHFT is safe in carefully selected HIV‐positive patients and outcomes are similar to those of HIV‐negative patients.